Trascender la presencia (Studia Poliana, 2018)
To transcend the presence.- In contrast to Heidegger's claim which establishes the end o f metaphysics, it is generally upheld that Polo's proposal regarding the expansion -through anthropology- of the metaphysic's own transcendental reach permits supersedence without lessening perennity. This widening requires not only a thematical explanation but also a methodical one, upon which the congruency both of metaphysics and of anthropology, as different types of philosophy for the transcendental, can be established. This method springs forth from the detection of the limiting character that revolves around mental presence. It is actuality understood as the least intellectual act in human knowledge, and deserts the intellective modality by means of superior intellectual acts.